PERUBAHAN PERMUKIMAN NELAYAN PASCA REKLAMASI PANTAI DI KELURAHAN LETTE, KECAMATAN MARISO MAKASSAR - Aidi Darmansyah; Sudaryono Sudaryono; Deva Fosterharoldas Swasto (Jurnal Teknosains, 2019)
Lette is one of the sub-districts in Mariso Subdistrict, Makassar City which has a suburban area and the community has a livelihood as a fisherman. The condition of the Tanjung Bunga coastal and coastal area has undergone a change, which used to be the territorial waters that are now largely transformed into land, this change is due to the ongoing coastal and coastal reclamation process in the area of Tanjung Bunga. To meet the need for urban space, Lette fishermen have no choice but to be relocated from their place of origin to the flats. This study aims to determine the spatial, cultural, socio-economic changes in the fishing settlement of Lette and the factors that drive these changes. This study uses an inductive-qualitative method with a phenomenological approach. The results of the study show that the changes that occur are changes in coastal space, changes in settlement space and the creation of a central business, tourism and entertainment area. Factors driving these changes are changes in fishing boat access and entry, dock circulation, catching areas that are not potential, domestic activities, spatial space utilization, bale-bale culture, informal fishing activities, and new economic space.